Management and 30-Day Mortality of Acute Coronary Syndrome in a Resource-Limited Setting: Insight From Ethiopia. A Prospective Cohort Study - Fanta, Korinan; Daba, Fekede Bekele; Asefa, Elsah Tegene; Melaku, Tsegaye; Chelkeba, Legese; Fekadu, Ginenus; Gudina, Esayas Kebede (Frontiers in Cardiovascular Medicine, 2021)
Background: Despite the fact that burden, risk factors, and clinical characteristics of acute coronary syndrome (ACS) have been studied widely in the developed countries, limited data are available from sub-Saharan Africa. Therefore, this study aimed at evaluating clinical characteristics, treatment, and 30-day mortality of patients with ACS admitted to tertiary hospitals in Ethiopia. Methods: A total of 181 ACS patients admitted to tertiary care hospitals in Ethiopia were enrolled from March 15 to November 15, 2018. Clinical characteristics, management, and 30-day mortality were evaluated by ACS subtypes. Cox-proportional hazard model was used to determine predictors of 30-day all-cause mortality and the p-value <0.05 was considered statistically significant. Results: The majority (61%) of the ACS patients were admitted with ST-elevation myocardial infarction (STEMI) and the mean age was 56 years with male predominance (62.4%). More than two-thirds (67.4%) of patients presented to the hospital after 12 hours of symptom onset. Dyslipidemia (48%) and hypertension (44%) were the most common risk factors identified. In-hospital dual antiplatelet and statin use was high (>90%); followed by beta-blockers (81%) and ACEIs (72%). Late reperfusion with PCI was done for only 13 (7.2%) and none of the patients received early reperfusion therapy. The 30-day all-cause mortality rate was 25.4%. On multivariate cox-proportional hazard model analysis, Older age (HR =1.03, 95% CI = 1.003-1.057), systolic blood pressure (HR=0.99, 95% CI =0.975-1.000), serum creatinine (HR=1.32 95% CI=1.056-1.643), Killip class > II (HR=4.62 95% CI=2.502-8.523), ejection fraction <40% (HR= 2.75 95% CI=1.463-5.162), and STEMI ((HR=2.72 95% CI=1.006-4.261) were independent predictors of 30-day mortality. Conclusions: The thirty-day all-cause mortality rate was unacceptably high which implies urgent needs to establish a nationwide program to reduce pre-hospital delay, promoting the use of guideline-directed medications, and increasing access to reperfusion therapy.